Finding True North in Ethical Practices in Information Service Provision in Academic Libraries in Uganda - Kaddu, Sarah B.; Ssekitto, Francis (Ghana Library Journal, 2023)
Ethical practices in information service provision have become integral for librarians and information professionals in  the ever-evolving landscape of information dissemination and access. These practices  encompass an array of principles  governing professional behaviours, ensuring moral conduct, and preventing  potential misconduct. This paper explores  the ethical practices and information services in the Makerere  University Business School (MUBS) library.  This study  adopted a qualitative research approach, with semi-structured interviews, observations, and  document analysis as the  data collection methods. The findings illuminated a comprehensive array of services  available within the MUBS library  context, including textbooks and eBooks short-term loans; reference books  and e-reference books; internet and WIFI;  current awareness; interlibrary loan; journals and e-journals access to  patrons; MUBS librarians’ dedication to principles  such as equitable access, privacy protection, and intellectual  property rights. Ethical dilemmas arising from  balancing intellectual freedom and responsible information  provision are also unveiled. These findings resonate with  global ethical considerations in librarianship,  reflecting libraries’ evolving roles in the digital age. The study’s insights  will inform MUBS library operations  and contribute to the scholarly discourse on ethical library practices. The research  implies that librarians’  ethical decisions impact service quality and user experiences.